MP35: Acceptability of older patients' self-assessment in the emergency department (ACCEPTED) – a randomized cross-over trial. (May 2019) - Boucher, V.; Lamontagne, M.; Lee, J.; Carmichael, P.; Déry, J.; Émond, M.
Abstract : Introduction : It is recommended that seniors consulting to the Emergency Department (ED) undergo a comprehensive geriatric screening, which is difficult for most EDs. Patient self-assessment using electronic tablet could be an interesting solution to this issue. However, the acceptability of self-assessment by older ED patients remains unknown. Assessing acceptability is a fundamental step in evaluating new interventions. The main objective of this project is to compare the acceptability of older patient self-assessment in the ED to that of a standard assessment made by a professional, according to seniors and their caregivers.Methods : Design: This randomized crossover design cohort study took place between May and July 2018.Participants : 1) Patients aged ≥65 years consulting to the ED, 2) their caregiver, when present.Measurements : Patients performed self-assessment of their frailty, cognitive and functional status using an electronic tablet. Acceptability was measured using the Treatment Acceptability and Preferences (TAP) questionnaires.Analyses : Descriptive analyses were performed for sociodemographic variables. Scores were adjusted for confounding variables using multivariate linear regression. Thematic content analysis was performed by two independent analysts for qualitative data collected in the TAP's open-ended question.Results : A total of 67 patients were included in this study. Mean age was 75.5 ± 8.0 and 55.2% of participants were women. Adjusted mean TAP scores for RA evaluation and patient self-assessment were 2.36 and 2.20, respectively. We found no difference between the two types of evaluations (p = 0.0831). When patients are stratified by age groups, patients aged 85 and over (n = 11) showed a difference between the TAPs scores, 2.27 for RA evaluation and 1.72 for patient self-assessment (p = 0.0053). Our qualitative data shows that this might be attributed to the use of technology, rather than to the self-assessment itself. Data from 9 caregivers showed a 2.42 mean TAP score for RA evaluation and 2.44 for self-assessment. However, this relatively small sample size prevented us to perform statistical tests.Conclusion : Our results show that older patients find self-assessment in the ED using an electronic tablet just as acceptable as a standard evaluation by a professional.